Gap in the prognostic impact of short physical performance battery among phenotypes of heart failure. (15th August 2022) - Iwatsu, Kotaro; Ikeda, Tsutomu; Matsumura, Koichi; Ashikawa, Hironobu; Fujita, Ryoko; Takabayashi, Kensuke; Kitaguchi, Shoji; Nohara, Ryuji
Abstract: Background: The Short Physical Performance Battery (SPPB) has been reported to predict clinical outcomes in patients with heart failure (HF). However, whether the discriminative capacity of SPPB score for adverse outcomes varies according to the phenotypes of HF, such as HF with reduced, mid-range, and preserved left-ventricular ejection fraction (HFrEF, HFmrEF, and HFpEF) remains unclear. The aim of this study was to investigate the difference in discriminative capacity of SPPB score for predicting 2-year mortality among phenotypes of HF. Methods: We consecutively enrolled 542 adult patients admitted for HF (HFrEF, n  = 187; HFmrEF, n  = 94; HFpEF, n  = 261). The patients underwent SPPB score when discharged from hospital. The primary endpoint was all-cause mortality during the 2 years after hospital discharge. We assessed the discriminative capacity of SPPB score for predicting mortality by using receiver operating characteristic (ROC) curve analysis. Results: A total of 95 events (17.5%) occurred during the follow-up period. The area under the curve of ROC (95% confidence interval) was 0.80 (0.71–0.88) in HFrEF, 0.61 (0.46–0.76) in HFmrEF, and 0.70 (0.61–0.79) in HFpEF group. After adjustment for potential confounders, the hazard ratios (95% confidence interval) of the lower SPPB score were 5.38 (2.34–14.6) in HFrEF group, 1.12 (0.36–3.29) in HFmrEF group, and 3.19 (1.68–6.22) in HFpEF group. Conclusions: Prognostic value of SPPB score varies according to the HF phenotype. SPPB score predicts mortality in patients with HFrEF and HFpEF, but not in patients with HFmrEF. These findings lead to more precise risk prediction by SPPB score in patients with HF. Graphical abstract: Image 1 Highlights: Prognostic value of SPPB score varied according to the HF phenotype. SPPB score predicted mortality in patients with HFrEF and HFpEF, but not in patients with HFmrEF. Accounting for LVEF in patients with HF leads to more accurate risk stratification by using the SPPB score.